Altered Proliferative Response by T Lymphocytes of Ly-6A (Sca-1) Null Mice - Stanford, William L. (The Rockefeller University Press, 1997)
Ly-6A is a murine antigen which is implicated in lymphocyte activation and may be involved in activation of hematopoietic stem cells. Antibody cross-linking studies and antisense experiments have suggested that Ly-6A is a lymphocyte coactivation molecule. To better understand the function of Ly-6A, we used gene targeting to produce Ly-6A null mice which are healthy and have normal numbers and percentages of hematopoietic lineages. However, T lymphocytes from Ly-6A–deficient animals proliferate at a significantly higher rate in response to antigens and mitogens than wild-type littermates. In addition, Ly-6A mutant splenocytes generate more cytotoxic T lymphocytes compared to wild-type splenocytes when cocultured with alloantigen. This enhanced proliferation is not due to alterations in kinetics of response, sensitivity to stimulant concentration, or cytokine production by the T cell population, and is manifest in both in vivo and in vitro T cell responses. Moreover, T cells from Ly-6A–deficient animals exhibit a prolonged proliferative response to antigen stimulation, thereby suggesting that Ly-6A acts to downmodulate lymphocyte responses.